ACTIVE FAULTS, SEISMICITY AND RECENT FRACTURING IN THE LITHOSPHERE OF THE BAIKAL RIFT SYSTEM - Sherman S.I.; Dem'yanovich V.M.; Lysak S.V. (My University, 2004)
A map of major active faults has been constructed for the Baikal rift system (BRS). Recent active faults are identified using seismological data. The BRS seismicity of the past 40 years is statistically analyzed. Areas of a “stable” concentration of epicenters are revealed. On this basis, a zone of recent fracturing of the lithosphere is identified and its relation to active and developing faults of the BRS is analyzed. The zone of the lithosphere fracturing is a major tectonic structure, which controls both the recent seismic process and the reactivation of ancient faults. It is demonstrated that the available seismological data can provide a basis for a detailed classification of faults by degree of their tectonic activity. Regularities in the distribution of strong earthquakes along the zone of the recent fracturing of the lithosphere are established, as well as regularities in the distribution of strong and weak seismic events relative to transform and other faults. The degree of the fault reactivation is determined by their spatial closeness to the axial zone of the recent rupturing of the lithosphere.
Keywords: Active faults; Fracturing of the lithosphere; Zone of fracturing; Seismicity; Earthquake epicenter field; Baikal rift system